THE CHARM OF INDONESIAN IN LOCAL MENUS: A CASE STUDY OF THE USE OF INDONESIAN IN MENUS ON CONSUMER PURCHASE INTEREST AT THE MELIO ENIM HOTEL - Nur Shabrina Reznani; Andhika Chandra Lesmana; Samuel Hamonangan (Politeknik Pariwisata Palembang, 2026)
This study aims to determine the extent of influence of the use of Indonesian in the food & beverage menu book on consumer purchasing interest at the Melio Hotel, Muara Enim Regency, Sumatra Province. This study uses a descriptive research method with a quantitative approach. The data were collected using questionnaires, observations, interviews, documentation and literature studies. The sample in the study amounted to 98 respondents who were consumers. Based on the results of data processing using SPSS, it was found that the use of Indonesian in the menu had a positive effect on purchasing interest, Indonesian language on menus still has strong existence and consumers respond well to menu information written in Indonesian. However, the use of foreign languages should be balanced with appreciation and preservation of Indonesian language as part of national identity